THE EFFECT OF WORK ENVIRONMENT AND JOB SATISFACTION ON JOB PERFORMANCE THROUGH LOYALTY AMONG EMPLOYEES OF UPTD PUSKESMAS PARIGI - Theodorus, Gabriella Franly; Siregar, Robert Tua; Romy, Elly; Edward, Yusuf Ronny; Matondang, Sofiyan (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2026)
This study aims to examine the influence of work environment and job satisfaction on employee performance with loyalty serving as an intervening variable at UPTD Puskesmas Parigi. As public health institutions increasingly emphasize service quality, employee attitudes, work atmosphere, and organizational commitment become critical components that determine performance outcomes. The study uses a quantitative approach with a census sampling method involving all 52 employees at Puskesmas Parigi. Data were collected through structured questionnaires and analyzed using multiple linear regression and Sobel test procedures to assess both direct and mediating effects. The results reveal that the work environment has a positive and significant impact on both loyalty and performance, indicating that comfortable, safe, and supportive workplace conditions contribute directly to improved performance. Job satisfaction significantly influences performance but does not significantly influence loyalty, suggesting that satisfaction enhances productivity but may not necessarily strengthen commitment. Employee loyalty significantly contributes to performance, confirming its role in increasing employees’ willingness to give their best. Furthermore, loyalty does not mediate the influence of work environment on performance but does mediate the relationship between job satisfaction and performance. These findings highlight the importance of cultivating a positive work atmosphere and managing satisfaction proactively to ensure optimal employee performance in healthcare settings.